Infection in an aging population - Kline, Kimberly A. (2016)
The global population is rapidly aging. Currently, 566 million people are ≥65 years old worldwide, with estimates of nearly 1.5 billion by 2050, particularly in developing countries. Infections constitute a third of mortality in people ≥65 years old. Moreover, lengthening life spans correlate with increased time in hospitals or long-term care facilities and exposure to drug-resistant pathogens. Indeed, the risk of nosocomial infections increases with age, independent of duration spent in healthcare facilities. In this review, we summarize our understanding of how the aging immune system relates to bacterial infections. We highlight the most prevalent infections affecting aging populations including pneumonia, urinary tract infections, and wound infections and make recommendations for future research into infection in aging populations.